(3GdfgGjI aj ZQjH GdMOjK hGdCKQs - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s
(3ChdgG (B:s
(3jHOC HMQa GdQGA HGH GdQGA eY GdgeRI (B: (3ai MOjK Ydi jUa CHG HcQ (B: (3cfJ ddOjf QCHkG CQCH (B: (3GdLeY hGdTO s
(3BNQgG (B:s
(3jfJgi HHGH GdjGA eY GdgGA hGdjGA GdYjf GdegedI UbdY ef HdGO Gdjef LYdg dge Je GdLRA GdKGdK ef cJGH GdfgGjI ai ZQjH GdMOjK hGdCKQ hHJeGeg fLR SGFQ GdcJGH hddg GdMeO hGdefI hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg GdWjHjf GdWGgQjf s
(3YdjgG Jedc ZjQ eDQN HGSe YHO GdQMef Hf ShjO GdeGdcis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B272 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B174s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1989s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG RNGQa s
Keywords: (3GdMOjK h GdeUWdMs